A review on the role of QRIS and digital wallets in facilitating MSME transactions in Indonesia - Widjanarko, Wirawan (Goodwood Publishing, 2025)
Purpose: This literature review aims to develop hypotheses for future researchers conducting research related to the ease of transactions in MSMEs. Research Methodology: The approach used in this literature review was descriptive and qualitative. The data collection technique uses literature studies or conducts a literature review of relevant previous articles. The data used in this study are secondary data, sourced from academic online media such as Thomson Reuters Journals, Sage, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Springer, Web of Science, Sinta Journals, DOAJ, EBSCO, Google Scholar, and digital reference books. Empirical data were used to support the phenomena observed in this study. Results: The results of this study are as follows: 1) QRIS affects the ease of transactions in micro, small, and medium enterprises; and 2) digital wallets affect the ease of transactions in micro, small, and medium enterprises. Limitations: This study is limited to micro-, small-, and medium-sized enterprises. Contribution: This study contributes to the understanding of the factors influencing the ease of transactions in MSMEs, with a focus on factors related to the use of QRIS and digital wallets. Novelty: This study provides new insights into other factors that influence the ease of transactions for MSMEs, especially in Indonesia. Thus, it can be used as a reference material in future studies.